Penggunaan Merek Air Minum dalam Kemasan oleh Depot Air Minum Isi Ulang Perspektif Fatwa DSN MUI No. 1 Tahun 2005 Tentang Hak Kekayaan Intelektual (Studi Kasus Desa Cipar-Pari Timur Kecamatan Sultan Daulat Kota Subulussalam) - Lara Nopi Dayanti; Uswatun Hasanah (UNES Law Review, 2023)
This research aims to find out the law behind the use of the brand of bottled drinking water Aqua by the business owner of UD refill drinking water depot. Laras. This research was conducted in Cipar-Pari Timur Village, Sultan Daulat Subdistrict, Subulussalam City. The subjects in this study were refill water depot business owners and their workers. In accordance with the results of interviews with the object of research, it is known that the reason behind the use of the Aqua brand is the lack of knowledge of the owner of the refill drinking water depot on the existence of brand rights, besides that it is also because the owner of the refill drinking water depot does not provide gallons for refills at the drinking water depot so that people use the gallons they have before to fill in the refill drinking water depot. Distributors or Aqua bottled drinking water business owners are also more assertive in maintaining assets that are already owned, so that there are no events that can harm them.